Reducing N Fertilization without Yield Penalties in Maize with a Commercially Available Seed Dressing - Stefania Codruta Maris; Federico Capra; Federico Ardenti; Marcello E. Chiodini; Roberta Boselli; Eren Taskin; Edoardo Puglisi; Chiara Bertora; Lorenzo Poggianella; Stefano Amaducci; Vincenzo Tabaglio; Andrea Fiorini (Agronomy, 2021)
Introducing smart and sustainable tools for climate change adaptation and mitigation is a major need to support agriculture’s productivity potential. We assessed the effects of the processed gypsum seed dressing SOP® COCUS MAIZE+ (SCM), combined with a gradient of N fertilization rates (i.e., 0%, 70% equal to 160 kg N ha−1, and 100% equal to 230 kg N ha−1) in maize (Zea mays L.), on: (i) grain yield, (ii) root length density (RLD) and diameter class length (DCL), (iii) biodiversity of soil bacteria and fungi, and (iv) Greenhouse Gases (GHGs, i.e., N2O, CO2, and CH4) emission. Grain yield increased with SCM by 1 Mg ha−1 (+8%). The same occurred for overall RLD (+12%) and DCL of very fine, fine, and medium root classes. At anthesis, soil microbial biodiversity was not affected by treatments, suggesting earlier plant-rhizosphere interactions. Soil GHGs showed that (i) the main driver of N losses as N2O is the N-fertilization level, and (ii) decreasing N-fertilization in maize from 100% to 70% decreased N2O emissions by 509 mg N-N2O m−2 y−1. Since maize grain yield under SCM with 70% N-fertilization was similar to that under Control with 100% N-fertilization, we concluded that under our experimental conditions SCM may be used for reducing N input (−30%) and N2O emissions (−23%), while contemporarily maintaining maize yield. Hence, SCM can be considered an available tool to improve agriculture’s alignment to the United Nation Sustainable Development Goals (UN SDGs) and to comply with Europe’s Farm to Fork strategy for reducing N-fertilizer inputs.